Recent Progress in UAV-AI Remote Sensing (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
This reprint delves into the cutting-edge intersection of Unmanned Aerial Vehicles (UAV) and Artificial Intelligence (AI), offering a comprehensive look at how these technologies are revolutionizing vegetation monitoring, target tracking, and various other applications. Featuring 15 in-depth articles, this Special Issue explores the potential of UAV multispectral and hyperspectral imagery for real-time dynamic monitoring and for the development of innovative methods for data interpretation. Some key features include, but are not limited to, the following: Focus on the application of AI techniques to process and model data from UAV sensors. Detailed analysis of UAV imagery in vegetation growth monitoring and dynamic target tracking. Topics include crop physical and chemical parameter inversion, crop growth monitoring, building extraction, and pest and disease forecasting. Novel approaches to extracting valuable information from UAV imagery. Essential reading for researchers, professionals, and students interested in UAV and AI integration.